High‐rise residential building ventilation in cold climates: A review of ventilation system types and their impact on measured building performance. (18th November 2022) - Berquist, Justin; Cassidy, Noah; Touchie, Marianne; O'Brien, William; Fine, Jamie
Abstract: Ventilation system performance in high‐rise multi‐unit residential buildings (MURBs) has a significant impact on resident wellbeing. While the importance of ventilation is well established, it is commonly overlooked since underperformance often goes undetected. This article presents a review and synthesis of ventilation system performance in high‐rise MURBs located in cold climates as it relates to the three pillars of sustainability: economic (capital and operational cost), social (airflow control, indoor environmental quality, and occupant behavior and interactions), and ecological (energy and carbon). A meta‐analysis revealed previous ventilation system designs generally prioritized economic sustainability, specifically, capital cost. However, priorities have recently shifted toward social and ecological sustainability. While this shift is positive, there is insufficient empirical evidence showing which ventilation system most effectively supports it. The decentralized heat/energy recovery ventilator (HRV/ERV) system shows the potential to improve upon the social and ecological sustainability of previous designs, such as the centralized pressurized corridor system, but the interconnected nature of performance metrics can cause improvements to one to negatively impact others. Therefore, further research is required to enhance ventilation system performance in cold climate, high‐rise MURBs, and facilitate decision‐making while designing and retrofitting these systems.